Diagnostic Model in Polycystic Ovarian Syndrome Based on Traditional Iranian Medicine and Common Medicine - Maryam Rohani; Shapour Badiee Aval; Ali Taghipour; Maliheh Amirian; Shokouh-Sadat Hamedi; Mandana Tavakkoli; Seyyedeh-Atiyeh Naeemi; Malihe Motavasselian (Mashhad University of Medical Sciences, 2017)
Introduction: Polycystic ovarian syndrome (PCOS) is the most common endocrine disorder in reproductive-aged women. Since no similar study was published so far to evaluate the symptoms and diagnostic model of the disease from the view of Iranian traditional medicine, therefore, this study was performed to adapt the symptoms and achieve the diagnostic model of PCOS from the view of Iranian traditional medicine in order to achieve the prevention methods and more effective treatment in these patients. Methods: In this comparative study with content analysis approach, all signs and symptoms of PCOS from the view of classic medicine were collected from Textbooks of Obstetrics and various papers and 14 Textbooks of Traditional Medicine. Thereafter, the relevant codes were produced by the software program Max.Qda2. PCOS was classified based on these signs. Results: Given diagnostic criteria of PCOS in classic medicine and searching for signs associated with these criteria in Textbooks of Traditional Persian Medicine, extremely warm dystemperament or warm and dry in uterine, ovaries or in the whole body, extremely cold dystemperament or cold dystemperament with phlegm in reproductive organs or in the whole body associated with the concentrations of humors lead to the signs relevant to hyperandrogenism and menstruation disorder. Conclusion: Based on the findings, two major patterns were proposed for patients. The first group included those who have "cold" and "humid" dominance while the second group consists of those with "heat" dominance in their temperament. Each group with respect to their temperament need to specific and different pharmacological or non-pharmacological treatments and strategies according to warm and cold degree of drug constituents.